2022
DOI: 10.1186/s13287-022-03034-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and their derived small extracellular vesicles for COVID-19 treatment

Abstract: Since December 2019, the coronavirus (COVID-19) pandemic has imposed huge burdens to the whole world, seriously affecting global economic growth, and threatening people’s lives and health. At present, some therapeutic regimens are available for treatment of COVID-19 pneumonia, including antiviral therapy, immunity therapy, anticoagulant therapy, and others. Among them, injection of mesenchymal stem cells (MSCs) is currently a promising therapy. The preclinical studies and clinical trials using MSCs and small e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…MSCs are now widely investigated in various diseases, such as kidney disease, osteoarthritis, and even COVID-19 [5,33,34]. In recent years, researchers have started to focus on the role of MSCs on PF.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are now widely investigated in various diseases, such as kidney disease, osteoarthritis, and even COVID-19 [5,33,34]. In recent years, researchers have started to focus on the role of MSCs on PF.…”
Section: Discussionmentioning
confidence: 99%
“…The found that these stem cells were well tolerated in this severe pneumonia [179]. Similarly, the therapeutic option of MSCs in other respiratory disease patients such as COPD, ARDS and COVID-19 patients is well reported [180][181][182][183]. Interestingly, a recent phase I study assessed the tolerability and safety of allogeneic MSC infusion in cystic fibrosis patients and found that the allogeneic MSC intravenous infusions is welltolerated and safe [184].…”
Section: Most Recent Progress In the Application Of Mesenchymal Strom...mentioning
confidence: 96%
“…The advantages of EVs from human cells or cell lines as therapeutic agents are the potential to cross biological barriers, cell-specific function, and their low immunogenicity because they do not display exogenous factors ( 84 , 85 ). The in vitro generation and modulation of mesenchymal stem cell-derived EVs for Covid-19 treatment and autoimmune diseases is currently tested in clinical and pre-clinical studies ( 86 , 87 ), with no severe adverse effects described so far. In preclinical models, MSC- or Treg-derived EVs have been successfully used in an animal model of rheumatoid arthritis ( 88 , 89 ).…”
Section: Translational Application Of Extracellular Vesicles Targetin...mentioning
confidence: 99%